Prognostic impact of low allelic ratio FLT3-ITD and NPM1 mutation in acute myeloid leukemia - Sakaguchi, Masahiro (Blood Adv, 2018)
In the opinion of the European LeukemiaNet (ELN), nucleophosmin member 1 gene mutation (NPM1 mut)–positive acute myeloid leukemia (AML) with an fms-like kinase 3-internal tandem duplication (FLT3-ITD) allele ratio (AR) <0.5 (low AR) has a favorable prognosis, and allogeneic hematopoietic stem cell transplant (allo-HSCT) in the first complete remission (CR1) period is not actively recommended. We studied 147 patients with FLT3-ITD gene mutation–positive AML, dividing them into those with low AR and those with AR of ≥0.5 (high AR), and examined the prognostic impact according to allo-HSCT in CR1. Although FLT3-ITD AR and NPM1 mut are used in the prognostic stratification, we found that NPM1 mut–positive AML with FLT3-ITD low AR was not associated with favorable outcome (overall survival [OS], 41.3%). Moreover, patients in this group who underwent allo-HSCT in CR1 had a significantly more favorable outcome than those who did not (relapse-free survival [RFS] P = .013; OS P = .003). Multivariate analysis identified allo-HSCT in CR1 as the sole favorable prognostic factor (RFS P < .001; OS P < .001). The present study found that prognosis was unfavorable in NPM1 mut–positive AML with FLT3-ITD low AR when allo-HSCT was not carried out in CR1.